Depositional Paleoenvironments and Implications on the Occurrence of the Shahejie Formation Source Rock in the Langgu Sag, Bohai Bay Basin - Cao, Yijun; Diao, Fan; Zou, Huayao (Frontiers in Earth Science, 2022)
The fourth (Es4) and the third (Es3) members of the Eocene Shahejie Formation (Es) are potential source rock intervals in the Langgu hydrocarbon-generating sag. However, the mechanism of source rock occurrence remains poorly understood. In this study, 50 core samples of the Es (21 of Es4 and 29 of Es3) from the Langgu sag were conducted on total organic carbon (TOC) determination, Rock-Eval pyrolysis, carbon isotope of organic matter (δ13COM), carbon (δ13CCarb) and oxygen (δ18OCarb) isotope of carbonate, bulk mineral compositions, and major and trace element concentrations to characterize the depositional environments and reveal the controlling factors of organic matter enrichment during the deposition of the Es source rock intervals. The Es4 was deposited under relatively hydrologically closed saline lake under arid climate. In comparison, semihumid to humid paleolimnological conditions prevailed during the deposition of Es3, which accompanied with enhanced chemical weathering and relatively low paleosalinity. Redox proxies indicate that the Es4 rock was deposited in a relatively stronger reducing environments compared to the Es3. Relatively 13C enrichment in the organic matter (δ13COM is as high as –23%) of the Es3 rock is mainly associated with promoted primary productivity triggered by an increased input/recycling of nutrients favored by semihumid climate and hydrologically open paleolake conditions. The hydrogen index (HI) versus Δδ13CCarb-OM (the diﬀerence between the δ13CCarb and δ13COM) indicate that enhanced preservation and promoted primary productivity seemed to be the main factor in the accumulation of organic matter during the deposition of Es4 and Es3 in the Langgu sag, respectively. Nevertheless, low to medium hydrocarbon-generating potential for Es mudstone indicates that dilution played a significant role in the formation of high-quality source rock apart from the influences of productivity and preservation. In comparison, Es source rock of limited petroleum potential could be ascribed to dilution associated with high sedimentation rate.